2016
DOI: 10.1007/s11606-016-3886-9
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Professional Burnout and Quality and Safety in Healthcare: A Meta-Analysis

Abstract: This is the first study to systematically, quantitatively analyze the links between healthcare provider burnout and healthcare quality and safety across disciplines. Provider burnout shows consistent negative relationships with perceived quality (including patient satisfaction), quality indicators, and perceptions of safety. Though the effects are small to medium, the findings highlight the importance of effective burnout interventions for healthcare providers. Moderator analyses suggest contextual factors to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
455
4
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 597 publications
(490 citation statements)
references
References 56 publications
18
455
4
13
Order By: Relevance
“…Globally, there is a crisis in the recruitment and retention of mental health nurses, putting extra pressure on those who are left to deliver quality services (Redknap et al ). International studies have associated high staff turnover, decreased work efficiency and poor quality of service delivery with burnout (Salyers et al ; Yang et al ). Burnout is a cross‐cultural phenomenon and is considered a common problem among mental health professionals, with service providers reporting between 21% and 67% of staff experiencing burnout (Foster et al ; Morse et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Globally, there is a crisis in the recruitment and retention of mental health nurses, putting extra pressure on those who are left to deliver quality services (Redknap et al ). International studies have associated high staff turnover, decreased work efficiency and poor quality of service delivery with burnout (Salyers et al ; Yang et al ). Burnout is a cross‐cultural phenomenon and is considered a common problem among mental health professionals, with service providers reporting between 21% and 67% of staff experiencing burnout (Foster et al ; Morse et al ).…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that a combination of both programmes leads to better results on burnout reduction (Awa et al ; Günüşen & Üstün ). Studies examining the effects of burnout prevention programmes have in the main shown a decrease in the level of burnout or in its EE, DP, and PA subscales (Kravits et al ; Onan et al ; Salyers et al ). For example, Salyers et al () found EE and DP were reduced among mental health professionals after implementing a one‐day workshop on burnout prevention.…”
Section: Introductionmentioning
confidence: 99%
“…A confluence of factors including organizational demands, environmental effects, and personal resilience are likely at play in determining the individual well-being (Edwards & Burnard 2003;Johnson et al 2018). Some have argued that mounting pressures in the NHS in recent times have added to these risks by increasing the incidence of harmful and adverse events, staff turnover, and negatively impacting psychological well-being (van Bogaert et al 2013;Hall et al 2016;Hanrahan et al 2010;Kapur et al 2018;Salyers et al 2017). Indeed, nurses working in mental health settings are at a high risk of being assaulted and the lifetime risk is approaching 100% (Bowers et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis by Salyers et al evaluated eighty-two studies and reported a small to moderate negative association between provider burnout and quality of care measures, with 7% of quality measure variance and 5% of safety measure variance attributed to provider burnout. 72 Notably, Aiken et al have reported an observed 7% increase in patient mortality and 23% increase in the odds of nurse burnout for each additional patient added to a nurse’s workload. 73 Expounding on this work in multivariable analyses, Cimiotti et al reported that burnout carries a stronger association with health care-associated infections than does nurse staffing, with each 10% increase in burnout prevalence corresponding to 0.8 urinary tract infections and 1.6 surgical site infections per 1000 patients.…”
Section: Teamwork- and Resilience-driven Quality Improvementmentioning
confidence: 99%